Implementación de las normas internacionales de información financiera para pequeñas y medianas entidades (NIIF para las pymes), en la empresa AJ computación y su impacto tributario para el periodo 2014 - Topa Chuquitarco, Jessica Geoconda (2016)
Despite the growing economic progress presented by globalization and the development of international trade, many countries today are experiencing a severe economic crisis, businesses have lost market share, decisions made by their employers have not been the most appropriate due to the low credibility and transparency of financial statements reporting, this is because many companies have not yet implemented international accounting standards in its accounting. AJ Computing is no exception applies GAAP have not been allowed to obtain reliable financial information, suitable for the economic life of the entity….